Genetic parameters for body weight in meat quail - Barbieri, A. [UNESP]; Ono, R. K. [UNESP]; Cursino, L. L. [UNESP]; Farah, M. M. [UNESP]; Pires, M. P. [UNESP]; Bertipaglia, T. S. [UNESP]; Pires, A. V.; Cavani, L. [UNESP]; Carreno, L. O. D. [UNESP]; Fonseca, R. (Oxford Univ Press, 2015)
The aim of this study was to estimate genetic parameters for BW in meat quail at different ages. A total of 24,382 weight records from 3,652 quail, born between 2009 and 2011, were evaluated. Weekly BW was measured from hatch until 42 d of age. The genetic parameters were estimated by the restricted maximum likelihood method using a multivariate animal model. Heritability of BW ranged from 0.03 to 0.23. Genetic correlations were mainly high and positive. Selection for BW at 28 d of age yielded good indirect genetic progress in BW at 42 d of age.
Keywords: Genetic correlation; Coturnix coturnix; Heritability